An oral corpus of PL2: a new resource for research and teaching - Almeida Santos, Isabel (2016)
The relevance of empirical data for sustaining research on second language learning is undeniable. Given the strong reliance of the quality of research results on the quality of the data on which these are based, the careful organization of learners’ corpora is paramount. The PL2 Oral Corpus project aims to provide researchers with oral production data elicited according to the protocol described, thus allowing for descriptions of learners’ interlanguages, accross different areas of Portuguese grammar and usage, as well as a sustained definition of PL2 speakers’ proficiency levels. This data base may also ground and validate didactic and pedagogical projects.